21 The usefulness and acceptability of a personal-health record to young people with a life-limiting condition: a realist evaluation. (13th October 2019) - Diffin, Janet; Byrne, Bronagh; O'Halloran, Peter
Abstract : Background: Communication between young people (YP) with life-limiting conditions and healthcare professionals (HCPs) can be challenging, particularly during transition from children to adult services. 1 Personal-health records (PHRs) have the potential to increase YP's selfadvocacy 2 yet have not been evaluated thoroughly with this population. Aim: Use realist evaluation to test and refine a programme theory on how PHRs are thought to work with YP with a life-limiting condition. Methods: Qualitative study informed by realist evaluation. YP aged 16–24 years old living in Northern Ireland with a life-limiting condition were invited to use a PHR; semi-structured interviews conducted at three, six and nine months to examine acceptability and use. Framework method used for analysis. Results: Eight YP and two parents (on behalf of child) participated. 4/10 used the PHR; reasons included: (i) to help organise their care, (ii) feel more confident with communication, (iii) reduce the need to repeat details about condition(s)/medications, and (iv) manage health care when aspects of their lives were changing. PHR use depended on the level of need, desire for autonomy/self-management, and whether it brought benefits over how they currently managed their condition. Two additional contextual considerations which influenced PHR use were identified (i) YPs previous experiences in communication with HCPs, and (ii) the timing of the introduction of the PHR. Conclusion: PHRs may be useful for YP who wish to become more independent over management of their healthcare but should be targeted towards those who identify a need, and their usage supported by HCPs. Funder: Marie Curie.